2021
DOI: 10.3390/s21186131
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a Switch from Intermittently Scanned Continuous Glucose Monitoring (isCGM) to Real-Time (rt) CGM in Diabetes Type 1 Suboptimal Controlled Patients in Real-Life: A One-Year Prospective Study §

Abstract: The switch from intermittently scanned continuous glucose monitoring (isCGM) to real-time (rt) CGM could improve glycemic management in suboptimal controlled type 1 diabetes patients, but long-term study is lacking. We evaluated retrospectively the ambulatory glucose profile (AGP) in such patients after switching from Free Style Libre 1 (FSL1) to Dexcom G4 (DG4) biosensors over 1 year. Patients (n = 21, 43 ± 15 years, BMI 25 ± 5, HbA1c 8.1 ± 1.0%) had severe hypoglycemia and/or HbA1c ≥ 8%. AGP metrics (time-in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Large glucose variability might increase oxidative stress and inflammation, which cause endothelial cell damage 25 and increase cardiovascular risk 26 . Several studies have shown that rtCGM is superior to isCGM in terms of reducing the TBR, and improving the TIR and HbA1c levels in adult patients with type 1 diabetes 7 , 8 , 9 , 10 , 11 . Reddy et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Large glucose variability might increase oxidative stress and inflammation, which cause endothelial cell damage 25 and increase cardiovascular risk 26 . Several studies have shown that rtCGM is superior to isCGM in terms of reducing the TBR, and improving the TIR and HbA1c levels in adult patients with type 1 diabetes 7 , 8 , 9 , 10 , 11 . Reddy et al .…”
Section: Discussionmentioning
confidence: 99%
“… 7 and Préau et al . 10 reported that switching from isCGM to rtCGM reduced TBR and increased TIR in patients with type 1 diabetes, and suggested switching from isCGM to rtCGM as an alternative to changing the insulin delivery system in patients with suboptimal glycemic control. A 6‐month multicenter randomized controlled trial carried out by Visser et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ALERTT1 study showed that a switch from isCGM to rtCGM improved TIR in adults significantly after 6 months [ 9 ], while under sub-optimal control, such a switch leads to benefits in terms of hypoglycemia prevention but no significant reduction in hyperglycemia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%